Extreme Weights in Steinhaus Triangles - Brunat, Josep M.; Maureso, Montserrat (Electronic notes in discrete mathematics, 2016)
Let {0=w0<w1<w2<…<wm} be the set of weights of binary Steinhaus triangles of size n, and let Wi be the set of sequences in F2n that generate triangles of weight wi. In this paper we obtain the values of wi and the corresponding sets Wi for i∈{2,3,m}, and partial results for i=m−1.